Prevalence of injuries in elite swimmers: the role of discipline and training intensity - Holst-Christensen, T.; Nimb, S. K.; Eggers, A.; Rosenberg, M.; Lundström, J.; Kjær, M.; Magnusson, S. P.; Højfeldt, G. (BMJ Open Sport & Exercise Medicine, 2026)
Introduction Elite swimming is characterised by high training volumes, which increases the risk of overuse injuries, but detailed information on whether specific swim disciplines or the training intensity matters for the occurrence of injuries is sparse. This study aimed to describe the injury prevalence, incidence and distribution among elite swimmers and to identify potential risk factors.